Shah Waliullah’s influence on the thought of Sayyid Abul A‘la Mawdudi - Abul Kalam, Mohammad Shahed (Penerbit Universiti Kebangsaan Malaysia, 2010)
By utilizing the library research method, this paper aims at analysing the influences of Shah Waliullah on the thoughts of Sayyid Abul A‘la Mawdudi. Shah Waliullah (1703-1762) was one of those great Islamic thinkers who by the virtue of their knowledge and activities helped reconstruct the sociopolitical and religious thought in Islam. Waliullah bridged between medieval and modern Islam in India. He was a socio-political reformer, a great Islamic scholar, a Sufi, a reformist and an Islamic missionary worker, all at the same time. Mawdudi (1903-1979) was greatly influenced by the thought and teachings of Waliullah. He was an expounder of Islam during the 20th century. Both of them have presented Islam as a complete code of life with solutions to all problems faced by mankind. In line with Waliullah’s thought, Mawdudi chalked out a strategy to establish an Islamic State and initiated a powerful movement to translate Islamic ideology into a realizable term for the reconstruction of socio-political life in accordance with Islamic ideology. However, Mawdudi did not accept every thought of Waliullah uncritically. He disagreed with Waliullah on several issues including Islamic mysticism. Yet, similarities in their thoughts are overwhelming. Both initiated a process of socio-political change in their respective times, inspired by Islamic ideal. This paper focuses on the similarities of thought between the two scholars in terms of ideology, socio-political and religious reform, emphasis on the independent judgement or the Ijtihad.